Immune Checkpoint Inhibitor Associated Hepatotoxicity in Primary Liver Cancer Versus Other Cancers: A Systematic Review and Meta‐Analysis - Fu, Jianyang; Li, Wang-Zhong; McGrath, Nicole A.; Lai, Chunwei Walter; Brar, Gagandeep; Xiang, Yan-Qun; Xie, Changqing (Frontiers in Oncology, 2021)
Background: Overall risks of hepatotoxicity with immune checkpoint inhibitors (ICIs) have yet to be compared in primary liver cancers to other solid tumors. Methods: We reviewed data from the PubMed, Embase, and Scopus databases, and assessed the risk of hepatotoxicity associated with ICIs. Results: A total of 117 trials were eligible for the meta‐analysis, including 7 trials with primary liver cancers. The most common hepatotoxicity was ALT elevation (incidence of all grade 5.29%, 95% CI 4.52-6.20) and AST elevation (incidence of all grade 5.88%, 95% CI 4.96-6.97). The incidence of all grade ALT and AST elevation was 6.01% and 6.84% for anti-PD‐1 (95% CI 5.04-7.18/5.69-8.25) and 3.60% and 3.72% for anti-PD-L1 (95% CI 2.72-4.76/2.82-4.94; p< 0.001/p<0.001). The incidence of  grade 3 ALT and AST elevation was 1.54% and 1.48% for anti-PD‐1 (95% CI 1.19-1.58/1.07-2.04) and 1.03% and 1.08% for anti-PD-L1 (95% CI 0.71-1.51/0.80-1.45; p= 0.002/p<0.001). The incidence of all grade ALT and AST elevation was 13.3% and 14.2% in primary liver cancers (95% CI 11.1-16.0 and 9.93-20.36) vs. 4.92% and 5.38% in other solid tumors (95% CI 4.21-5.76 and 4.52-5.76 in other solid tumors; p <0.001 /p<0.001). Conclusion: Our study indicates that anti-PD-1 is associated with a higher risk of all‐ and high‐grade hepatotoxicity compared to anti-PD-L1, and primary liver cancers are associated with a higher risk of all‐ and high‐grade hepatotoxicity compared to other solid tumors.